KEPUTUSAN INVESTASI DAN PENDANAAN SERTA PENGARUHNYA TERHADAP NILAI PERUSAHAAN DI BEI - jurnal khitabah (KHITABAH: Khazanah Penelitian Perbankan Syariah, 2024)
This study examines the conditions of investment decisions, financing decisions, and firm value in manufacturing companies listed on the Indonesia Stock Exchange (IDX). Furthermore, it investigates the influence of investment and financing decisions on firm value, both partially and simultaneously, in this sector. The research adopts a quantitative approach using a descriptive associative method. The findings reveal that investment decisions (CPA/BVA) and financing decisions (DER) significantly affect firm value (PBV) in the manufacturing sub-sector companies.